Hungary : An Economic Survey. (Occasional Papers; Occasional Paper ;, 1982)
This paper presents an overview of the economy of Hungary. The paper highlights that during the Fifth Five-Year Plan (1976-80), actual growth rates for almost all major plan aggregates remained below the targets. The lower targets set for the increase in both consumption and investment in the 1976-80 plan relative to the rates achieved during 1971-75, reflected the government's policy of moderating the growth of domestic demand. The actual average annual growth rate for investment closely approximated, whereas that of private consumption fell far short of the plan targets.